Pemanfaatan Pohon Karier dalam Meningkatkan Pemahaman Siswa Memilih Studi Lanjut di UPTD SMP Negeri 10 Kupang Kelas IX Tahun Ajaran 2024/2025 - Filisianus Junasius Moman; Yovina Trisna Setia; Paula Rosalina Nanga; Liberti Dhingi Pui; Yosefina Sara Kian; Regina Deru Neto; Selomitha Rambu; Wilibald Lelan; Margaretha Dhiu (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
Education is a fundamental aspect in shaping the future of the younger generation, and choosing further studies after education at junior high school level is a crucial decision. At UPTD SMP Negeri 10 Kupang, many students, especially in class IX for the 2024/2025 academic year, face difficulties in determining their further study path. To help students plan their careers, implementing Guidance and Counseling (BK) services in the career field is very necessary, one of which is through creating a career tree. A career tree is a visual aid that depicts the career paths and educational pathways that students can pursue based on their interests and abilities. This method aims to provide students with a better understanding of the career options available, recognize their own potential, and plan strategic steps to achieve their career goals. The results of this activity show that making a career tree was successful in providing insight to students, helping them know themselves better, and motivating them to actively seek information about careers and further education. Creating a career tree has proven to be effective as a solution in planning the right career and further studies. Therefore, it is recommended to improve guidance and counseling services, implement career trees regularly, and involve parents and the community in supporting students' career development.